The Effect of Applying POSSE (Predict- Organize-Search-Summarize-Evaluate) on the Students’ Reading Comprehension - Eka Rejeki Maha; Berlin Sibarani (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2013)
This study was aimed at finding out The Effect of Applying POSSE (Predict-Organize-Search-Summarize-Evaluate) Strategy on the Students’ Reading Comprehension. This study used the experimental design. The population of this study was the students of SMA Negeri 2 Medan. There were sixty students taken as the sample of the research. This study was conducted with two randomized groups namely experimental and control group. The experimental group was taught by applying POSSE strategy while control group was taught without applying POSSE strategy. The instrument of collecting the data was multiple choice test which consists of 40 items. To obtain the reliability of the test, the researcher used Kuder-Richardson (KR-21). The calculation shows the reliability was 0.81(high). The data were analyzed by using t-test. The calculation shows that t-observed (4.76) is higher than t-table (2.00) at the level of significance (α) 0.05 with the degree of freedom (df) 58. Therefore, the null hypothesis (Ho) is rejected and alternative hypothesis (Ha) is accepted. It means that there was a significant effect of applying POSSE strategy on the students’ reading comprehension. Keywords: POSSE Strategy, Reading Comprehension.